Logit Analysis of Employee Turnover in a Remote Community - Holmes, R.H.; Pinfield, L.T. (Relations industrielles / Industrial Relations, 1984)
This paper presents an empirical test of a model of labor turnover with a particular application to remote communities in Canada.